Model Komunikasi Pemasaran Paguyuban Batik Tulis - Fera Nurficahyanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This study aims to find strategic model for marketing communications of Paguyuban Batik Tulis Giriloyo Bantul in increasing sales. Type of research is qualitative research. Data are collected by observation, document review and interview. The result shows that marketing communication strategy of Paguyuban Batik Tulis Giriloyo Bantul is still familial and simple. The biggest supporting factor in terms of marketing is Yogyakarta get new name predicate as the World Batik City so more people use batik. Inhibiting factor in the marketing communication strategy is lack of competence of marketing division.